2011
DOI: 10.2527/jas.2010-3354
|View full text |Cite
|
Sign up to set email alerts
|

Genetic structure and diversity among sheep breeds in the United States: Identification of the major gene pools1,2

Abstract: Understanding existing levels of genetic diversity of sheep breeds facilitates in situ and ex situ conservation activities. A comprehensive evaluation of US sheep breeds has not been previously performed; therefore, we evaluated the genetic diversity among and within 28 US sheep breeds. Both major and minor breeds were included in the analysis and consisted of 666 animals from 222 producers located in 38 states. The level of within-breed genetic diversity was variable and not dependent upon status of a breed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 20 publications
3
38
0
Order By: Relevance
“…This can be explained by the formation process of the populations, determined by common ancestry, due to their similar function in the sheep industry and supposed racial admixture (Blackburn et al, 2011). In a meta-analysis performed by Paiva et al (2011b), association among these populations was also confirmed, grouping them into the same cluster.…”
Section: Discussionmentioning
confidence: 75%
“…This can be explained by the formation process of the populations, determined by common ancestry, due to their similar function in the sheep industry and supposed racial admixture (Blackburn et al, 2011). In a meta-analysis performed by Paiva et al (2011b), association among these populations was also confirmed, grouping them into the same cluster.…”
Section: Discussionmentioning
confidence: 75%
“…The level of inbreeding recorded here for the Pedigree WM is an important observation, as Blackburn et al (2011) suggest that breeds with an inbreeding coefficient greater than 0.15 warrant close monitoring. The Nelson WM type, with a coefficient of inbreeding of 0.144, is also close to this value of 0.15, and so may be another population which needs to be carefully monitored.…”
Section: Discussionmentioning
confidence: 55%
“…Blackburn et al (2011) reported 13% variation among populations and Dixit et al (2011) found 16.5% of variation was due to between breed differences. This difference may be due to the comparatively low number of individual animals involved in the current study, or because this research has largely looked at variation between populations of different phenotypic types within the WM breed rather than difference between breeds per se.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Desert sheep comprise about 80% of the slaughtered sheep in Sudan which greatly contributes in supplying both local markets and exportation [1]. Gastrointestinal nematodes represent a major production problem for ruminant which might be due to a combination of several factors such as climate, level of dietary energy, age, and sheep general health [2,3]. Helminthiasis cause loss of production through mortality, weight loss and reduced meat production leading to serious industrial and economic losses [4].…”
Section: Introductionmentioning
confidence: 99%